2013
DOI: 10.5194/cp-9-2135-2013
|View full text |Cite
|
Sign up to set email alerts
|

Glacial fluctuations of the Indian monsoon and their relationship with North Atlantic climate: new data and modelling experiments

Abstract: Abstract. Several paleoclimate records such as from Chinese loess, speleothems or upwelling indicators in marine sediments present large variations of the Asian monsoon system during the last glaciation. Here, we present a new record from the northern Andaman Sea (core MD77-176) which shows the variations of the hydrological cycle of the Bay of Bengal. The high-resolution record of surface water δ18O dominantly reflects salinity changes and displays large millennial-scale oscillations over the period 40 000 to… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
101
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(108 citation statements)
references
References 111 publications
(148 reference statements)
7
101
0
Order By: Relevance
“…10). A similar circulation anomaly over Africa and the Arabian Sea was recently found in freshwater hosing experiments by Marzin et al 3 and, by means of atmosphere-only sensitivity experiments, could be attributed to anomalous sea surface temperature forcing in the tropical Atlantic ("tropical pathway"). Unrelated to the Indian summer monsoon an equivalent barotropic wave train propagating south-eastward from the northern North Atlantic source region is also found in the Heinrich Stadial winter circulation anomaly (Extended Data Fig.…”
Section: Indian Summer Monsoon Weakening and Atmospheric Atlantic Ocesupporting
confidence: 80%
See 1 more Smart Citation
“…10). A similar circulation anomaly over Africa and the Arabian Sea was recently found in freshwater hosing experiments by Marzin et al 3 and, by means of atmosphere-only sensitivity experiments, could be attributed to anomalous sea surface temperature forcing in the tropical Atlantic ("tropical pathway"). Unrelated to the Indian summer monsoon an equivalent barotropic wave train propagating south-eastward from the northern North Atlantic source region is also found in the Heinrich Stadial winter circulation anomaly (Extended Data Fig.…”
Section: Indian Summer Monsoon Weakening and Atmospheric Atlantic Ocesupporting
confidence: 80%
“…As part of the Hadley cell reorganization during Heinrich stadials, the Indian summer monsoon weakens. This weakening has been recently attributed to anomalous SST forcing in the tropical Atlantic that affects the Indian monsoon via a tropical atmospheric pathway 3 . Our model results suggest a rapid response of the Indian monsoon to North Atlantic abrupt events through both a stationary Rossby wave-train teleconnection that originates in the northern North Atlantic and a tropical atmospheric pathway (Methods).…”
mentioning
confidence: 97%
“…As evidenced over Terminations I and II and over the last 240 ka, δ 18 O atm variations are closely related to the dynamic of the low-latitude hydrological cycle (Wang et al, 2008;Severinghaus et al, 2009;Landais et al, 2007Landais et al, , 2010Landais et al, , 2013Cheng et al, 2009). Monsoons are influenced by orbital forcing, with a strong imprint of precession (Wang et al, 2008;Braconnot et al, 2008), but also by the millennial-scale variability (Wang et al, 2001;Marzin et al, 2013). The Heinrich event 1 is for instance associated with a weak monsoon interval (e.g.…”
Section: δOmentioning
confidence: 99%
“…The abrupt climate changes seen in our records correspond closely to the wet periods recorded in stalagmite d 18 O data from Brazil (Wang et al, , 2007, which also correspond to Heinrich events in the North Atlantic (Bond et al, 1997). Many studies have found that ISM and EASM precipitation patterns are related to variations in North Atlantic climate (Cosford et al, 2008;Deplazes et al, 2013;Marzin et al, 2013;Tierney and Pausata, 2015). The mechanism could explain the millennial-scale teleconnection between the North Atlantic, Asian monsoon region, and South America.…”
Section: Synchronous Long-term Changes In Ism and Easm And Abrupt CLmentioning
confidence: 64%